Eksperimen Berbasis Media Benda Konkret Kelas V Pada Mata Pelajaran IPA di SDN 3 Buluagung Tahun Pelajaran 2022-2023 - Arif Hariyanto (Tarunateach: Journal of Elementary School, 2023)
The low learning outcomes and interest of fifth grade students at SDN 3 Buluagung, Siliragung District, Banyuwangi Regency in science lessons is the background of this research. This condition is influenced by teachers not using appropriate methods and media. As a result, students are sleepy in learning in the classroom. Science subjects are learning that requires experiments and the use of real objects as an introduction to learning material. This study uses a class action research method that aims to improve student learning outcomes in science subjects in class V at SDN 3 Buluagung. This research carried out 2 cycles of learning improvement. After the learning improvement plan for cycle 1 was held, an average classical completeness of 61.1% was obtained with 45% of students completing their studies while 55% were below the KKM. In cycle 2 there was a very rapid development of student learning completeness where classical completeness was 83.5% or 81% complete in learning and 19% did not complete learning. From the results of these data, using concrete object-based experimental methods can improve student learning outcomes and interest. For this reason, researchers suggest using experimental methods with concrete object media to create innovative and fun learning so that students can easily understand.